2008
DOI: 10.1038/sj.bjc.6604152
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the androgen receptor is associated with reduced survival in hormone-refractory prostate cancer patients

Abstract: Cell line studies demonstrate that the PI3K/Akt pathway is upregulated in hormone-refractory prostate cancer (HRPC) and can result in phosphorylation of the androgen receptor (AR). The current study therefore aims to establish if this has relevance to the development of clinical HRPC. Immunohistochemistry was employed to investigate the expression and phosphorylation status of Akt and AR in matched hormone-sensitive and -refractory prostate cancer tumours from 68 patients. In the hormone-refractory tissue, onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 19 publications
(27 reference statements)
4
80
0
Order By: Relevance
“…All these samples were obtained with 8 weeks of biochemical relapse being diagnosed (two consecutive rises in PSA greater than 10%). Phosphorylated Akt expression is already available for this patient cohort (McCall et al, 2008).…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…All these samples were obtained with 8 weeks of biochemical relapse being diagnosed (two consecutive rises in PSA greater than 10%). Phosphorylated Akt expression is already available for this patient cohort (McCall et al, 2008).…”
Section: Patientsmentioning
confidence: 99%
“…Expression of phosphorylated Akt at serine 473 (activated Akt) for this cohort of patients had already been established in a previous study (McCall et al, 2008). Levels of phosphorylated Akt expression in tumours that expressed low levels of PTEN was higher compared to tumours that expressed high levels of PTEN (P ¼ 0.047).…”
Section: Hormone-sensitive Tumoursmentioning
confidence: 99%
See 1 more Smart Citation
“…Caution should also be taken when investigating AR-P in the literature as some of the phosphorylation sites are given different numbers, which can confuse the reader. For example, Ser210 is described as phosphorylated (Lin et al 2001b, McCall et al 2008, Shank et al 2008, Bryant et al 2011; however, when referring to the standard AR protein sequence (ANDR HUMAN, P10275), an arginine is found at this site, while in other studies, the same serine in question is referred to as Ser213 (Wen et al 2000, Nan et al 2003, Burgdorf et al 2004, Taneja et al 2005, Kim & Lee 2009, Lee 2009). In this review, the nomenclature used will correspond to the standard sequence to avoid such confusion.…”
Section: Serine Phosphorylationmentioning
confidence: 99%
“…The effects of Akt on AR do appear to depend on the number of times cell lines have been passaged; for example, in low passage LNCaP cells Akt inhibits AR, while in high passage cells Akt can activate the AR (Lin et al 2003), which might explain why different functional outcomes are being observed. Upon comparing matched hormone-sensitive and refractory clinical samples of PC in terms of AR-P (Ser213) and the Akt signalling pathway, positive associations between expression and decreased time to death, time to relapse and survival were found (McCall et al 2008). GSK-3b, which is inhibited by Akt-mediated phosphorylation, also mediates AR-P but inhibits transcriptional activity by impeding the interaction between the N and C terminal regions, without affecting localisation or stability (Salas et al 2004.…”
Section: Ar-p Under Androgen-depleted Conditionsmentioning
confidence: 99%